The effects of categorical and linguistic adaptation on binocular rivalry initial dominance - Pelekanos, Vassilis; Roumani, Daphne; Moutoussis, Konstantinos (Frontiers in Human Neuroscience, 2012)
Binocular rivalry is an intriguing visual phenomenon, in which perception alternates between two different monocular stimuli. There has been a long debate regarding the nature of the brain mechanisms behind it, with a special emphasis on whether they are low-level or reside at a higher level of the visual pathway. Prior adaptation to one of the two monocular stimuli is known to affect the initial dominant percept in the following dichoptic presentation. In the present work, we use three different types of adaptation in order to investigate how each one of them affects initial dominance during binocular rivalry. Adapting to a face or house stimulus which is identical to the one used during rivalry, leads to its consequent suppression, verifying previous findings. However, the adaptation used here is binocular, excluding the possibility of an eye-effect and showing that it is the specific stimulus that the brain is adapted to. In a second experiment, we also find suppression effects following adaptation to a different stimulus, which however belongs to the same category (face or house). In a final experiment in which participants are primed with the words ‘face’ or ‘house’, a small facilitatory effect is observed, which is, however, not statistically significant. Our results show that the outcome of binocular rivalry can be directly influenced by the prior presentation of visual and perhaps semantic stimuli, thus supporting the influence of higher-level, cognitive mechanisms on this very interesting perceptual phenomenon.